Floral Biology and Floral Visitors of Psychotria nilgiriensis var. astephana (Hook. f.) Deb et Gang. (Rubiaceae) from Kalakad Mundanthurai Tiger Reserve, Southern Western Ghats, India - Malleshappa, H.; Selva Singh Richard, P. (Indian Forester, 2011)
The present study is a preliminary work highlighting the floral biology of Psychotria nilgiriensis var. astephana (Hook. f.) Deb et Gang., where the floral characters such as the floral type, shape symmetry, colour, pollen morphology, pollen production, pollen - ovule ratio were studied. The flowers received 22 species of insects as diurnal floral visitors, predominantly butterflies (11 species) followed by bees (4 species), Flies (3 species), Ants (2 species), wasp and beetle (1 species each). Apis cerana, Appias wardi, Ypthima sp. and a species of wasp accounted for highest percentage of total visits to the blossoms. The most favourable temperature range with diverse community of floral visitors and maximum floral visits was between 25Â°C and 32Â°C. Observations based on the foraging behaviour of floral visitors as well as the number of visits shows that Appias wardi, Ypthima sp., wasp, Apiscerana and Lasioglossum sp. presumably the important pollinators of P. nilgiriensis var. astephana.